Brief Communication: Treatment Outcomes for Advanced Melanoma of Unknown Primary Compared With Melanoma With Known Primary - Persa, Oana Diana; Cecile Hassel, Jessical; Steeb, Theresa; Erdmann, Michael; Karimi, Bita; Stege, Henner; Klespe, Kai Christian; Schatton, Kerstin; Tomsitz, Dirk; Rübben, Albert; Thiem, Alexander; Berking, Carola; et al. (Journal of Immunotherapy, 2024)
Most patients with advanced melanomas have a known primary site [melanoma of known primary (MKP)]. However, 2%–9% of patients are diagnosed with melanoma metastasis of unknown primary (MUP). As MUP and MKP have similar UV-induced mutations and molecular signatures, it is proposed that the primary tumor has regressed completely in patients with MUP. As regression of the primary tumor could be indicative of enhanced recognition of melanoma antigens, we hypothesize that patients with advanced MUP have a better outcome compared with MKP. Patients with advanced MUP from 10 German university hospitals were retrospectively analyzed and matched with MKP based on the type of systemic treatment (BRAF and MEK inhibitors, PD-1 inhibitor monotherapy, combined CTLA-4 and PD-1 inhibitor therapy) therapy line (first or second line) and AJCC stage (IIIC, IV M1a–M1d). Three hundred thirty-seven patients with MUP were identified, and 152 treatments with PD-1 and CTLA-4 inhibitors, 142 treatments with PD-1 inhibitors, and 101 treatments with BRAF and MEK inhibitors were evaluated. Median time to treatment failure was significantly prolonged in patients with MUP treated with PD-1 monotherapy (17 mo, 95% CI: 9–25, P = 0.002) compared with MKP (5 mo, 95% CI: 3.4–6.6), as well as in MUP treated with combined PD-1 and CTLA-4 therapy (11 mo, 95% CI: 4.5–17.5, P < 0.0001) compared with MKP (4 mo, 95% CI: 2.9–5.1) Occurrence of immune-related adverse events and time to treatment failure for patients with BRAF and MEK inhibitors was similar in MKP and MUP. In our multicentre collective, patients with MUP have better outcomes under immunotherapy compared with MKP.
CRIS-Team Scopus Importer:2024-10-11
Keywords: immune checkpoint inhibitors; melanoma; targeted therapy